Monoclonal Antibodies Directed against Conserved Epitopes on the Nucleocapsid Protein and the Major Envelope Glycoprotein of Equine Arteritis Virus - Weiland, Emilie (American Society for Microbiology, 2000)
We recently developed a highly effective immunization procedure for the generation of monoclonal antibodies (MAbs) directed against the porcine reproductive and respiratory syndrome virus (E. Weiland, M. Wieczorek-Krohmer, D. Kohl, K. K. Conzelmann, and F. Weiland, Vet. Microbiol. 66:171–186, 1999). The same method was used to produce a panel of 16 MAbs specific for the equine arteritis virus (EAV). Ten MAbs were directed against the EAV nucleocapsid (N) protein, and five MAbs recognized the major viral envelope glycoprotein (G(L)). Two of the EAV G(L)-specific MAbs and one antibody of unknown specificity neutralized virus infectivity. A comparison of the reactivities of the MAbs with 1 U.S. and 22 newly obtained European field isolates of EAV demonstrated that all N-specific MAbs, the three nonneutralizing anti-G(L) MAbs, and the weakest neutralizing MAb (MAb E7/d15-c9) recognized conserved epitopes. In contrast, the two MAbs with the highest neutralization titers bound to 17 of 23 (MAb E6/A3) and 10 of 23 (MAb E7/d15-c1) of the field isolates. Ten of the virus isolates reacted with only one of these two MAbs, indicating that they recognized different epitopes. The G(L)-specific MAbs and the strongly neutralizing MAb of unknown specificity (MAb E6/A3) were used for the selection of neutralization-resistant (NR) virus variants. The observation that the E6/A3-specific NR virus variants were neutralized by MAb E7/d15-c1 and that MAb E6/A3 blocked the infectivity of the E7/d15-c1-specific NR escape mutant confirmed that these antibodies reacted with distinct antigenic sites. Immunoelectron microscopy revealed for the first time that the antigenic determinants recognized by the anti-G(L) MAbs were localized on the virion surface. Surprisingly, although the immunofluorescence signal obtained with the neutralizing antibodies was relatively weak, they mediated binding of about three times as much gold granules to the viral envelope than the nonneutralizing anti-G(L) MAbs.